Isolation, screening and identification of microorganisms having antimicrobial activity isolated from samples collected on seabed of Northeast Vietnam - Minh, Lê Thị Hồng; Quyên, Vũ Thị; Anh, Nguyễn Mai; Hương, Đoàn Thị Mai; Murphy, Brian T; Minh, Châu Văn; Cường, Phạm Văn (Vietnam Journal of Biotechnology, 2016)
Microorganisms are especially interested in due to the ability to produce secondary compounds with high-value applications. Plenty of novel and diverse chemical structures have been found in the bioactive substances of microorganisms. In this study, we isolated 143 strains of bacteria and actinomycetes from 161 samples including: sediments, sponges, soft corals, echinoderms and starfish collected from three sea areas of Viet Nam: Ha Long - Cat Ba; Co To - ThanhLan; Bai Tu Long. The strains were fermented in A1 medium and then fermentation broths were extracted 5 times with ethyl acetate. The extraction residue screening test using 7 reference strains isolated 15 target strains with the highest biological activity. Most of these strains have dramatic inhibition on Gram positive bacteria: Enterococcus faecalis ATCC29212; Bacillus cereus ATCC13245  and Candida albicans ATCC10231 with MIC values  ​​less than or equal to the MIC value of the reference antibiotic. In particular, strain G057 was active against S. enterica ATCC 13076 and G002 inhibited E. coli ATCC25922 with respective values  ​​MICG057 = 8 µg/ ml, MICG002 = 256µg/ ml; and three strains G115, G119, G120 showed the inhibitory effect towards P. aeruginosa ATCC27853 with respective values ​​MICG115 = 64 µg/ ml, MICG119 = 32 µg/ ml and MICG120 = 32 µg/ ml. All 15 strains were then subjected to morphological and phylogenetic investigations based on 16S rRNA gene sequences. The results showed that 9 of 15 strains G016, G017, G019, G043, G044, G047, G068, G119 and G120 belonged to Genus Micromonospora; strains G039 and G065 were identified as Genus Stretomyces; G002 was  identified as Bacillus; G057 was  identified as Nocardiopsis; G115 was in Photobacterium and G121 belonged Oceanisphaera.